2011
DOI: 10.1016/j.molcel.2011.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering 3′ss Selection in the Yeast Genome Reveals an RNA Thermosensor that Mediates Alternative Splicing

Abstract: Poor understanding of the spliceosomal mechanisms to select intronic 3' ends (3'ss) is a major obstacle to deciphering eukaryotic genomes. Here, we discern the rules for global 3'ss selection in yeast. We show that, in contrast to the uniformity of yeast splicing, the spliceosome uses all available 3'ss within a distance window from the intronic branch site (BS), and that in ∼70% of all possible 3'ss this is likely to be mediated by pre-mRNA structures. Our results reveal that one of these RNA folds acts as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
138
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 34 publications
11
138
1
1
Order By: Relevance
“…Secondary structure has been shown before to play a role in the recognition of some introns by the spliceosome (Deshler and Rossi 1991;Charpentier and Rosbash 1996;Gahura et al 2011;Meyer et al 2011), and structural features have been shown previously to aid in the computational prediction of splice sites (Patterson et al 2002;Marashi et al 2006). However, these computational methods only included information from a predicted optimal structure and did not contemplate a mechanistic hypothesis in the predictive model or the possibility of alternative 39ss selection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Secondary structure has been shown before to play a role in the recognition of some introns by the spliceosome (Deshler and Rossi 1991;Charpentier and Rosbash 1996;Gahura et al 2011;Meyer et al 2011), and structural features have been shown previously to aid in the computational prediction of splice sites (Patterson et al 2002;Marashi et al 2006). However, these computational methods only included information from a predicted optimal structure and did not contemplate a mechanistic hypothesis in the predictive model or the possibility of alternative 39ss selection.…”
Section: Discussionmentioning
confidence: 99%
“…In order to simulate normal growth conditions, we considered the structural properties of the sequence at 22°C (Materials and Methods). The effective distance between the BS and the HAG, calculated by subtracting the number of base positions contained in the optimal secondary structure (Materials and Methods), was not used as a feature to build the classifier but as a filter, as we have shown in a recent work that there is a maximum effective distance beyond which the HAG is never used as a 39ss (Meyer et al 2011; see Supplemental Table S1). …”
Section: Secondary Structures Help Explain 39ss Selectionmentioning
confidence: 99%
See 3 more Smart Citations